Answer:
![12\dfrac{7}{40}](https://tex.z-dn.net/?f=12%5Cdfrac%7B7%7D%7B40%7D)
Step-by-step explanation:
The given expression is
![\left(9\dfrac{7}{8} + 2\dfrac{4}{5}\right)-\dfrac{1}{2}](https://tex.z-dn.net/?f=%5Cleft%289%5Cdfrac%7B7%7D%7B8%7D%20%2B%202%5Cdfrac%7B4%7D%7B5%7D%5Cright%29-%5Cdfrac%7B1%7D%7B2%7D)
We need to find the simplified form of the given expression.
It can be rewritten as
![\left(9+\dfrac{7}{8} + 2+\dfrac{4}{5}\right)-\dfrac{1}{2}](https://tex.z-dn.net/?f=%5Cleft%289%2B%5Cdfrac%7B7%7D%7B8%7D%20%2B%202%2B%5Cdfrac%7B4%7D%7B5%7D%5Cright%29-%5Cdfrac%7B1%7D%7B2%7D)
Combine integers and fractions separately.
![(9+2)+(\dfrac{7}{8}+\dfrac{4}{5}-\dfrac{1}{2})](https://tex.z-dn.net/?f=%289%2B2%29%2B%28%5Cdfrac%7B7%7D%7B8%7D%2B%5Cdfrac%7B4%7D%7B5%7D-%5Cdfrac%7B1%7D%7B2%7D%29)
Taking LCM we get
![11+\dfrac{35+32-20}{40}](https://tex.z-dn.net/?f=11%2B%5Cdfrac%7B35%2B32-20%7D%7B40%7D)
![11+\dfrac{47}{40}](https://tex.z-dn.net/?f=11%2B%5Cdfrac%7B47%7D%7B40%7D)
In can be written as
![11+\dfrac{40+7}{40}](https://tex.z-dn.net/?f=11%2B%5Cdfrac%7B40%2B7%7D%7B40%7D)
![11+1+\dfrac{7}{40}](https://tex.z-dn.net/?f=11%2B1%2B%5Cdfrac%7B7%7D%7B40%7D)
![12+\dfrac{7}{40}](https://tex.z-dn.net/?f=12%2B%5Cdfrac%7B7%7D%7B40%7D)
![12\dfrac{7}{40}](https://tex.z-dn.net/?f=12%5Cdfrac%7B7%7D%7B40%7D)
Therefore, the expression
is equivalent to the given expression.
Answer:
6 2/3
Step-by-step explanation:
2 2/5 * 2 7/9
Change each number to an improper fraction
2 2/5 = (5*2+2)/5 = 12/5
2 7/9 = (9*2+7) = 25/9
12/5 * 25/9
Rewriting
25/5 * 12/9
5/1 * 4/3
20/3
Now changing to a mixed number
3 goes into 20 6 times with 2 left over
6 2/3
Answer:
r = 49
Step-by-step explanation:
The answer is B because the formula would be 850+(415*24) and the sum of that would be 10810.
Answer: .9
Step-by-step explanation:
You divide by 100 and get .9